Manual penanaman selasih (Ocimum Basilicum L.) menggunakan kaedah keratan batang - Yunus, Muhamad Fahmi; Ponari, Md Hoirul Azri; Shahari, Rozilawati; Salleh, Mohd Syahmi (2021)
The disclosure contains a manual on how to propagate Selasih, a medicinal plant widely used in Malaysia and other tropical countries